Pronominal choice: Indonesian diglossic code-switching on the Kick Andy show - Stuart Mannix Foster; Alistair Welsh (Universitas Pendidikan Indonesia, 2023)
Indonesian language contains a variety of pronouns and pronoun substitutes which enable speakers to position themselves in a variety of ways in relation to others for communicative purposes. Factors such as social standing, age, gender and cultural background influence pronominal choice but also reflect language alternation between standardised formal and informal Indonesian, a phenomenon known as diglossic code-switching. To study this, we examine the effects of pronominal choice by speakers on an episode of the popular Indonesian television talk show, Kick Andy. We first apply quantitative Discourse Analysis to sample conversations to identify the range of pronominal choice by speakers and instances of diglossic and English code-switching. Next we examine the use of diglossic code-switching through qualitative Conversation Analysis, to explore how speakers index themselves and others through individual linguistic choices of pronoun selection. In this study, we apply social positioning theory as a useful framework to analyse these dynamics. We detail how pronouns reflect social positioning of speakers and serve as a key indicator of societal power dynamics that broadly link to cultural norms. Our study contributes to sociolinguistic literature arguing that pronominal choice in Indonesian language is closely linked to diglossic code-switching.Â